Knowledge, attitude and behavioral intention to act regarding HIV infection and prevention in immigrants from the former Soviet Union in Germany: a comparative study with the native population - Kouznetsov, Laura; Matterne, Uwe; Crispin, Alexander; Ruzicka, Thomas; Zippel, Stefan; Kuznetsov, Alexander V. (Journal of immigrant and minority health, 2013)
In Germany, immigrants from Former Soviet Union (FSU) countries represent one of the largest immigrant groups. Some FSU countries face the highest HIV prevalence in the region of Eastern Europe and Central Asia. However, the HIV knowledge, attitude and behavioral intent have not been investigated in FSU immigrants compared to the native population yet. A cross-sectional anonymous survey among 1,205 FSU immigrants and 435 native Germans (aged 18-65 years) in Bavaria. Data analysis from the participating 435 (36 %) immigrants and 334 (76.8 %) natives showed that the immigrants were less knowledgeable (p < .001) about HIV transmission (median score 8 vs. 9, ranged from 0 to 10) and HIV prevention (4 vs. 5, ranged from 0 to 6) than the native Germans, especially with regard to HIV transmission during anal (67 vs. 79.1 %; OR = 1.86 [1.32-2.62]) and oral (49.7 vs. 61.8 %; OR = 1.63 [1.21-2.20]) intercourse and showed a high misconception rate. Age and education were associated with knowledge about sexual HIV transmission; male gender, age and education with HIV prevention by single-use of needles/syringes. In case of a suspected HIV contraction, fewer immigrants would request a test; in case of a confirmed HIV diagnosis fewer would use a condom or inform their sexual partner(s). This first comparative study indicates an urgent need for HIV/AIDS education among FSU immigrants.
Published online: 30 June 2012
Gesehen am 09.09.2021